Оспорювання батьківства після смерті особи, яка записана батьком дитини - Супрун, Т. С.; Suprun, T. S. (Право і безпека. - 2016. - № 1 (60). - С. 140–145, 2016)
Виконано науковий аналіз норм щодо оспорювання батьківства особи, яка записана батьком дитини, після її смерті. Надано практичні рекомендації щодо захисту прав спадкоємців цієї особи, покликані полегшити їх застосування. Зроблено висновок, що оспорювання батьківства у таких випадках значно ускладнене через вади механізму доведення спадкоємцями померлої особи своїх позовних вимог. Цей механізм потребує розширення з урахуванням норм цивільного процесуального законодавства.

Scientific analysis of the provisions of the Article 137 of the Family Code of Ukraine on challenging paternity after the death of a person registered as the child’s father has been accomplished. The author argues that because of the problems of applying, these norms are not widely used in practice, as well do not have sufficient scientific development. The objective of the article is the scientific analysis of the provisions of the Article 137 of the Family Code of Ukraine, which will facilitate their application and provision of practical recommendations on the protection of the heirs of a person registered as the child’s father. The author has proved that the Family Code of Ukraine establishes three reasons for challenging paternity after the death of a person registered as the child’s father by other persons (in particular by the heirs). They are: 1) submission by a person vita matris a written statement to a notary to disclaim his paternity (p. 1 of the Art. 137); 2) presenting by a person vita matris the claim in court to withdraw the registration of him as the father of the child from the birth record of the child with transferring the successors to these rights (p. 2 of the Art. 137); 3) the lack of information about recording him as the child’s father with valid reasons (p. 3 of the Art. 137). In other circumstances, nobody has the right to contest the paternity of another person, even if there is sufficient evidence. The author has provided practical recommendations on the protection of the heirs of the person intended to facilitate their use. It is concluded that challenging paternity in such cases is considerably hampered by shortcomings of the mechanism of proving as heirs of the deceased man of the claims. This mechanism needs to be expanded considering the norms of civil procedural legislation.

Выполнен научный анализ норм об оспаривании отцовства лица, которое записано отцом ребёнка, после его смерти. Даны практические рекомендации по защите прав наследников этого лица, призванные облегчить применение этих норм. Сделан вывод, что оспаривание отцовства в таких случаях значительно затруднено из-за недостатков механизма доказывания наследниками умершего лица своих исковых требований. Этот механизм нуждается в расширении с учётом норм гражданского процессуального законодательства.
Challenging paternity after the death of a person registered as the child’s father
Оспаривание отцовства после смерти лица, записанного отцом ребёнка
Супрун, Т. С. Оспорювання батьківства після смерті особи, яка записана батьком дитини / Т. С. Супрун,// Право і безпека. - 2016. - № 1 (60). - С. 140–145.
Suprun, T.S. (2016), “Challenging paternity after the death of a person registered as the child’s father” [“Osporiuvannia batkivstva pislia smerti osoby, yaka zapysana batkom dytyny”], Pravo i Bezpeka, No. 1, pp. 140–145.
Keywords: Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; оспорювання батьківства; особа, яка записана батьком дитини; актовий запис про народження; спадкоємці; спадкодавець; докази; доказування; challenging paternity; person registered as the child’s father; birth record; heirs; legator; evidence; proving; оспаривание отцовства; лицо, которое записано отцом ребёнка; актовая запись о рождении; наследники; наследодатель; доказательства; доказывание